Accelerated Cranioplasty with Perforator-preserved Split Flap Sandwiched Plate for Treatment of Infected Cranial Defects. Issue 4 (8th April 2022) - Okada, Yoshimoto; Narushima, Mitsunaga; Banda, Chihena H.; Danno, Kanako; Mitsui, Kohei; Shiraishi, Makoto; Shiba, Masato; Suzuki, Yume; Ishiura, Ryohei
Abstract : Summary: Large cranial vault defects are challenging to manage due to the need to balance infection control, skin coverage, and restoration of the protective mechanical rigidity of the skull while also ensuring good head and neck aesthetic results. Conventional-staged treatment requires a long time period that includes debridement and scalp skin defect coverage with flaps as a first step, followed by definitive plate reconstruction 3–9 months later after infection control and flap atrophy resolution. We report a case of successful early cranioplasty in a factory worker who developed a large full-thickness cranial skull defect following artificial dura infection. Reconstruction was performed in two stages using an anterolateral thigh (ALT) flap. In the first stage, the scalp defect was covered with an ALT flap to close the skin following debridement. In the second stage performed 6 weeks later, the ALT flap was split into adiposal and adipocutaneous flaps to sandwich a computer-aided design custom-made titanium plate with an opening for the perforator to complete the cranioplasty. The patient successfully returned to work without recurrence of infection with 1-year follow-up. We report this case to demonstrate the utility of adipocutaneous flap plate sandwiching techniques in providing well-vascularized cover for early definitive cranial reconstruction and accelerated patient recovery.